Developing Digital Portfolios To Enhance Employability And Career Success : A Community Service Program For High School Students And Fresh Graduates In Tasikmalaya - Andini, Dina; Kusnandar, Hasan Fahmi; Andriati, Yumi Sri; Sumarni, Reny; Faizal, Riza; Abdillah, Wildan Army; Marlina, Lina (Information Technology and Science (ITScience), 2024)
High school students and fresh graduates searching for employment often lack the confidence to create competitive application documents due to their limited work experience. This community service program, conducted at Transmart Mall Tasikmalaya, aimed to enhance the skills of high school students and fresh graduates in creating digital portfolios. The goal was to boost their confidence in job applications, increase their competitiveness in securing careers that align with their aspirations, and ultimately reduce unemployment rates. The program utilized a participatory method through seminars and workshops. Participants were taught the importance of creating portfolios that attract recruiters' attention and were guided to create their own portfolios using the CakeResume platform. Evaluation was conducted through pre and post training questionnaires distributed via Google Forms sent through the workshop group. The results showed a significant increase in participants' understanding of the importance of portfolios, an improvement in their confidence in creating digital portfolios, and high satisfaction with the community service workshop. Moreover, the participatory approach used in this program was effective in achieving the set objectives, particularly in enhancing participants' employability. The program's implications for local industries and companies include providing practical insights and valuable networking opportunities for participants.